DISTRIBUTION OF LARVAL AND POSTLARVAL ANTARCTIC FISHES AROUND ELEPHANT ISLAND AND BRANSFIELD STRAIT - ANTARCTICA. - Sinque, Chossi; Koblitz, Sigrid; Costa, Laura Marília (Revista Nerítica, 1986)
Distribution and abundance of larval and postlarval Antarctic fishes sampled by plankton nets, from the Oceanographic R/V “ BARÃO DE TEFFÉ” , around Elephant Island and Bransfield Strait, during the southern summer 1983/84 (PROANTAR II) and 1984/85 (PROANTAR III), were analysed. All the ichthyoplankton was composed of Nototheniidae (Pleuragramma antarcticum, Notothenia kempi, Notothenia larseni, Notothenia gibberifrons); Paralepididae (Notolepis coatsi); Myctophidae (Electrona antarctica) and Channichthidae (Champsocephalus gunnari). Of these P. antarcticum was the most abundant species followed by E. antarctica. The greatest diversity of species (5) was found around Elephant Island. DISTRIBUIÇÃO DE LARVAS E PÓS-LARVAS DE PEIXES ANTÁRTICOS AO REDOR DA ILHA ELEFANTE E ESTREITO DE BRANSFIELD — ANTÁRTICA. Distribuição e abundância de larvas e pós-larvas de peixes antárticos coletadas com redes de plâncton, a bordo do NAPOc “Barão de Teffé” , ao redor da Ilha Elefante e Estreito de Bransfield, durante o verão autral 1983/84 (PROANTAR II) e 1984/85 (PROANTAR III), foram analisados. O ictioplâncton era constituído de Nototheniidae (Pleuragramma antarcticum, Notothenia kempi, Notothenia larseni, Notothenia gibberifrons); Paralepididae (Notolepis coatsi); Myctophidae (Electrons antarctica) e Channichthyidae (Champsccephalus gunnari). A espécie mais abundante foi P. antarcticum, seguida de E. antarctica. O maior número de espécies (5) foi encontrado ao redor da Ilha Elefante.